2019
DOI: 10.12688/f1000research.18538.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of urea, creatinine and blood parameters in patients with pneumonia diagnosed with chronic obstructive pulmonary disease

Abstract: This study aimed to investigate the diagnostic value of urea, Background: creatinine and other blood parameters in patients with pneumonia diagnosed with chronic obstructive pulmonary disease (COPD) for the first time.In this retrospective study, patients who had been diagnosed Methods: with COPD for the first time and were diagnosed with pneumonia were included. A total of 193 patients were divided into three groups as COPD + pneumonia (n=123), COPD (n=36) and pneumonia (n=34).In total, 59 women (48.0%) and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…[12][13][14][15] Urea (ure) is produced when proteins break down in mammals' bodies. 16 Recent research has shown that measuring levels of urea in saliva can be used as an effective way to diagnose various illnesses such as kidney problems, 10,17,18 lung disease, [19][20][21] infections, 22,23 diabetes mellitus, 11,24,25 cancer, 26 hypertension, 25,27 and others. The current method for detecting salivary urea involves using absorption spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Urea (ure) is produced when proteins break down in mammals' bodies. 16 Recent research has shown that measuring levels of urea in saliva can be used as an effective way to diagnose various illnesses such as kidney problems, 10,17,18 lung disease, [19][20][21] infections, 22,23 diabetes mellitus, 11,24,25 cancer, 26 hypertension, 25,27 and others. The current method for detecting salivary urea involves using absorption spectrometers.…”
Section: Introductionmentioning
confidence: 99%